Skill versus content: using Twitter in the literature classroom - Zainal, Zainor Izat; Mohd Deni, Ann Rosnida (2017)
In the past decade or so, Twitter has been integrated in the classroom practice, in line with the rise of social networking sites and their popularity with students. Many studies conducted on the use of Twitter in the classroom have verified its beneficial effects in improving learners’ motivation, engagement and learning. This small-scale study, which adopted a mixed-method approach, reports students’ perceptions on the use of Twitter in two different literature in English subjects – one considered as a skill-based subject whereas one is a content-based subject. Data gathered through analyses of students’ tweets and a survey questionnaire administered found that 1) students were more active Tweeting in the content-based subject and that 2) students were less comfortable sharing their thoughts and ideas in Twitter in the skill-based subject. These findings imply that the nature of a course has an impact on the students’ willingness and perceptions of the use of Twitter. Suggestions are forwarded for future applications of Twitter in the literature classroom.